Web-Based Expert System for Diagnosing Rabies Disease - Meiarni Situkkir (SEAN Institute, 2024)
This study discusses the design and creation of an expert system application to diagnose rabies in dogs using the certainty factor method and utilizing computers as a tool in providing consultation services on rabies. Expert system capabilities can be obtained by implementing an algorithm that will be determined by its performance. The expert system model that is created is then to help diagnose rabies early and to make it easier to serve pets without having to leave the house. In addition, with this program, it can help a veterinarian's task in serving his patients, especially dogs. After the implementation of the Certainty Factor method, an expert system application is produced that can identify rabies in dogs from several symptom inputs. This expert system can be developed if the input data is continuously updated so that rabies in dogs that are found can be even more.